Optimization of the MgOSiO2 binding system for fiber-cement production with cellulosic reinforcing elements. (5th September 2016) - Mármol, Gonzalo; Savastano, Holmer; Tashima, Mauro M.; Provis, John L.
Abstract: A range of MgO and SiO2 blends mixed with water are analyzed to develop clinker-free fiber-cement products reinforced with cellulosic fibers. The target is the development of a binder which is not chemically aggressive to the fibers, but which develops high mechanical strength Mechanical performance of the materials developed is not only influenced by magnesium silicate hydrate ( M - S -H) gel content, but is more related to the void content within the paste due to unreacted water, meaning that the gel-space ratio concept is valuable in describing the compressive strengths of these materials. A higher MgO content in the mix formulation leads to M - S -H gels with increased Mg/Si ratio. The Mg/Si ratio also increases over time for each mix, indicated by changes in the gel structure as reaction is not yet complete after 28 days. SEM shows a heterogeneous microstructure which also has regions of high Si content. The 60 wt%MgO-40 wt%SiO2 system is chosen as the optimal formulation since it is the least alkaline binder with high mechanical strength. Bending tests on pastes reinforced with cellulosic pulps prove the efficiency of this binder, which preserves the reinforcing capacity of the fibers much better than Portland cement pastes after 200 cycles of accelerated ageing. Graphical abstract: Highlights: MgOSiO2 cement presents higher compressive strength than Portland cement at 28 days, for a water/cement ratio of 0.5. MgO and SiO2 cement display low pH values compared to Portland cement, below 11, at 7 days. For MgOSiO2 systems, mechanical performance is not only related magnesium-silicate-hydrate gel content, being more associated to the void content. MgOSiO2 binder protects fibers reinforcing capacity compared to Portland cement pastes after 200 cycles of accelerating ageing.